PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PRIMA SOEKA BUANA BEKASI - Veritia Veritia; Lili Sularmi; Feb Amni Hayati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The aim of this research is to determine the influence of work discipline and work environment on employee performance at PT. Prima Soeaka Buana. The research method used was quantitative. The sampling technique used was saturated sampling, and a total of 60 respondents were obtained as the sample. Data analysis included validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient, and hypothesis testing. Work discipline has a significant effect on employee performance with a simple linear regression equation of Y = 23.668 + 0.465X1, and a correlation coefficient of 0.457. The determination coefficient value is 20.9%, and the hypothesis test resulted in a t-value > t-table, or (3.914 > 1.671). Furthermore, the work environment also has a significant effect on employee performance with a simple linear regression equation of Y = 15.170 + 0.661X2, and a correlation coefficient of 0.723. The determination coefficient value is 52.3%, and the hypothesis test resulted in a t-value > t-table, or (7.968 > 1.671). Simultaneously, work discipline and work environment significantly influence employee performance with a multiple linear regression equation of Y = 3.697 + 0.338X1 + 0.603X2, and a correlation coefficient of 0.793. The determination coefficient value is 62.9%, while the remaining 37.1% is influenced by other factors. The hypothesis test resulted in an F-value > F-table, or (48.302 > 3.159).